The single beacon: progresses in understanding Earth as an exoplanet using DSCOVR/EPIC observations - Jian, Xun; Gu, Lixiang; Fan, Siteng; Bartlett, Stuart J.; Yang, Jiani; Jiang, Jonathan H.; Luo, Yangcheng; Yung, Yuk L. (Frontiers in Remote Sensing, 2025)
Almost 6000 exoplanets have thus far been confirmed, revolutionizing our understanding of planetary habitability. Yet, despite the identification of Earth-like exoplanets, definitive evidence of extraterrestrial life remains elusive. Studying Earth, the only confirmed habitable and inhabited planet, as a proxy exoplanet provides critical insights for interpreting forthcoming exoplanet direct-imaging data. Observations from the Deep Space Climate Observatory/Earth Polychromatic Imaging Camera (DSCOVR/EPIC), located at the first Sun-Earth Lagrangian point (L1), offer a unique opportunity to analyze Earth’s full-disk, single-point multi-spectrum light curves. Here, we review progress that treat EPIC data as if Earth were an unresolved, distant world. These studies reveal information about planetary rotation, cloud patterns, and surface types. Autocorrelation of the time series recovers the 24 h rotation period, while principal component analysis (PCA) highlights the land-ocean spectral contrast, enabling the reconstruction of a coarse two-dimensional surface map. Modeling studies further quantify the contributions of different planetary surfaces and clouds to Earth’s observable brightness, with low-level clouds playing a dominant role. Additionally, the effects of Earth’s atmosphere, particularly within strong oxygen bands, have been simulated and evaluated. The rich temporal–spectral “light-curve complexity” produced by its heterogeneous surface and dynamic atmosphere has emerged as a practical, observation-based metric of habitability. Comparisons with simulations and other solar system planets demonstrate that Earth’s light curves exhibit the highest complexity, underscoring its unique status as the only known habitable and inhabited exoplanet. These findings provide a valuable observational baseline for future exoplanet studies, refining our ability to recognize life-supporting worlds beyond the Solar System.